Arrested Coalescence: A Tool to Explore Tissue Rheology - Sotiris Samatas; Martí Planasdemunt-Hospital; David Oriola (Biophysica)
Tissue spheroids are self-organised 3D cellular aggregates that serve as a versatile platform in tissue engineering. While numerous high-throughput methods exist to characterise the cellular function of tissue spheroids, equivalent techniques for the mechanical characterisation are still lacking. In this review, we focus on tissue fusion— a simple, fast, and inexpensive method to characterise the rheology of tissue spheroids. We begin by discussing the implications of tissue rheology in development and disease, followed by a detailed explanation of how the phenomenon of arrested coalescence can be used to explore the rheology of tissue spheroids. Finally, we present different theoretical models that, when combined with experimental data, allow us to extract rheological information.